Ignition of fuel based on filter cake - Valiullin T. R. Timur Radisovich; Vershinina K. Yu. Kseniya Yurievna; Lyrshchikov S. Yu. Sergey Yurievich; Shevyrev S. A. Sergey Aleksandrovich (2017, 2017)
Title screen